2005
DOI: 10.1016/j.devcel.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Follistatin:Activin Complex Reveals Antagonism of Both Type I and Type II Receptor Binding

Abstract: TGF-beta ligands stimulate diverse cellular differentiation and growth responses by signaling through type I and II receptors. Ligand antagonists, such as follistatin, block signaling and are essential regulators of physiological responses. Here we report the structure of activin A, a TGF-beta ligand, bound to the high-affinity antagonist follistatin. Two follistatin molecules encircle activin, neutralizing the ligand by burying one-third of its residues and its receptor binding sites. Previous studies have su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
276
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(284 citation statements)
references
References 54 publications
6
276
1
1
Order By: Relevance
“…Materials-Purified human activin A, inhibin A, the extracellular domain of mouse ALK4 (ALK4-ECD), ActRIIB (ActRIIB-ECD), and mouse follistatin 288 (Fst 288) were produced by our laboratory (35,36). The CHO-Flp-in cell line and pcDNA5 plasmid used for cloning and establishment of isogenic stable cell lines were purchased from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Materials-Purified human activin A, inhibin A, the extracellular domain of mouse ALK4 (ALK4-ECD), ActRIIB (ActRIIB-ECD), and mouse follistatin 288 (Fst 288) were produced by our laboratory (35,36). The CHO-Flp-in cell line and pcDNA5 plasmid used for cloning and establishment of isogenic stable cell lines were purchased from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…the residues determining binding affinity and specificity) are still poorly understood. In follistatin-activin complex, two follistatin monomers surround the dimeric ligand and bury the binding sites for type I and type II receptors (15,16). Mutational analysis revealed that only residues at the type II receptor-binding surface of activin are critical for high affinity follistatin binding, and the interaction surfaces of activin for type II receptors and follistatin are overlapping but not identical (17).…”
mentioning
confidence: 99%
“…They also bind and inactivate myostatin and some bone morphogenetic proteins with varying degrees of affinity (14). Structural studies of the follistatin-activin complex have elucidated the basis for this interaction and provided clues about the determinants of follistatin binding to other ligands (15,16). The follistatin gene comprising 6 exons produces two alternatively spliced mRNA transcripts and the corresponding proteins of 315 or 288 amino acids (FS315 or FS288) (17, 18).…”
mentioning
confidence: 99%